Reasoning on choreographies and capability requirements. (3rd April 2008) - Baldoni, Matteo; Baroglio, Cristina; Martelli, Alberto; Patti, Viviana; , Claudio Schifanella
A typical problem of research in the area of service oriented systems is the composition of a set of services for executing a complex task. In this paper, we face an instance of this problem in which a set of parties (be their peers, agents or systems) have to interact according to a given choreography. In particular, we mean to exploit the role definitions contained in the choreography for realising interaction policies that can be executed by the involved parties. In this case, it is necessary that the choreography captures not only the interactive behaviour of the system as a whole but that the role definitions contain also a set of requirements of capabilities that the parties should exhibit, where by the term 'capability' we mean the skill of doing something or of making some condition become true. Such capabilities have the two-fold aim of connecting the interactive behaviour to be shown by the role player to its internal state and of making the policy executable.